The role of algae, fungi, and insect-derived proteins and bioactive peptides in preventive and clinical nutrition - Yimam, Mohammed Ahmed; Andreini, Martina; Carnevale, Sara; Muscaritoli, Maurizio (Frontiers in Nutrition, 2024)
The current global trend in the nutrition, epidemiologic and demographic transitions collectively alarms the need to pursue a sustainable protein diet that respects ecosystem and biodiversity from alternative sources, such as algae, fungi and edible insects. Then, changing the nutrition reality is extremely important to impede the global syndemic of obesity, undernutrition and climate change. This review aims to synthesize the published literature on the potential roles of alternative proteins and their derived bioactive peptides in preventive and clinical nutrition, identify research gaps and inform future research areas. Google Scholar and PubMed databases from their inception up to 30 June 2024 were searched using keywords to access pertinent articles published in English language for the review.Overall, proteins derived from algae, fungi, and edible insects are high-quality proteins as animal sources and demonstrate significant potential as a sustainable source of bioactive peptides, which are metabolically potent and have negligible adverse effects. They show promise to prevent and treat diseases associated with oxidative stress, obesity, diabetes, cancer, cardiovascular disease (especially hypertension), and neurodegenerative diseases. Given the abundance of algae, fungi and insect peptides performed in vitro or in vivo animals, further clinical studies are needed to fully establish their safety, efficacy and practical application in preventive and clinical nutrition. Additionally, social and behavioral change communication strategies would be important to increase health awareness of nutritional benefits and promote consumer acceptance of alternative protein sources.